A spot test for determination of residual TBA levels in 18F-radiotracers for human use using Dragendorff reagent. Issue 41 (1st October 2020) - Tanzey, Sean S.; Mossine, Andrew V.; Sowa, Alexandra R.; Torres, Jovany; Brooks, Allen F.; Sanford, Melanie S.; Scott, Peter J. H.
Abstract : A TLC spot test for determining residual TBA levels in positron emission tomography (PET) radiotracer formulations has been developed using Dragendorff reagent. Proof-of-concept is demonstrated by quantification of residual TBA in 6-[ 18 F]fluoro-DOPA. Abstract : When utilizing [ 18 F]tetrabutylammonium fluoride ([ 18 F]TBAF) in the synthesis of 18 F-labeled radiotracers for clinical positron emission tomography (PET) imaging, it is necessary to confirm that residual TBA levels in formulated doses do not exceed established specifications (≤2.6 mg per patient dose). Historically this has been accomplished using HPLC, but this is time consuming for short-lived PET radiotracers and limited by the need for expensive equipment. This motivated us to introduce a TLC spot test for determining residual TBA, and we have developed a new method which employs the Dragendorff reagent. Herein we report details of the TLC method and use it to quantify residual TBA in different formulations of 6-[ 18 F]fluoro-DOPA.